EFFECT OF THE TREATMENT OF RICE SEED INFECTED BY XANTHOMONAS ORYZAE PV. ORYZAE ON GROWTH AND YIELD OF RICE IN THE FIELD - Ahmad Zamzami; Satriyas Ilyas (Universitas Sembilanbelas November Kolaka, 2017)
This research aimed to study the effect of treatment of rice seed infected with X. oryzae pv. Oryzae naturally to control bacterial leaf blight and to increase growth and yield of rice in the field. The research used Slit plot design with the main plot of variety consisting of IR64 and Ciherang, while the subplot is a seed treatment consisting of control, bactericide 0.2% (Agrept 20WP), 1% citronella oil, biological agent Pseudomonas diminuta (McFarland IV scale ), matriconditioning + Agrept 0.2%, matriconditioning + 1% citronella oil, and matriconditioning + P. diminuta. Although seed treatment has not been able to control the bacterial leaf blight, it can increase the growth of seed and yield. Treatment of matriconditioning + Agrept 0.2% can increase the seed viability and dry weight of seedlings. Height of seedlings can be increased by the treatment of citronella oil, biological agents P. diminuta, matriconditioning + agrept 0.2%, and matriconditioning + 1% citronella oil. Treatment of citronella oil, matriconditioning + P. diminuta, biological agents P. diminuta, and matriconditioning + Agrept 0.2% can increase the estimated yield of ubinan/CCE harvest